Integrating Zep Quiz into IPAS Instruction to Enhance Fourth Grade Students’ Critical Thinking Skills - Muslimin, Muslimin (Journal of Education and Computer Applications, 2025)
This study aims to improve fourth-grade students’ critical thinking skills through the implementation of Zep Quiz in Integrated Science and Social Studies (IPAS) learning. Employing a Classroom Action Research (CAR) design, the study was conducted in three cycles, each comprising the stages of planning, action implementation, observation, and reflection. The research involved 23 students, consisting of 14 boys and 9 girls. Data were collected using teacher and student activity observation sheets and a critical thinking skills test administered at the end of each cycle. The results indicated a consistent increase in students’ critical thinking performance: the average score improved from 68.26 (56.52% mastery) in Cycle I to 77.04 (78.26% mastery) in Cycle II, and finally to 86.09 (91.30% mastery) in Cycle III. Teacher and student activities also showed progressive improvement, moving from the “fair” to the “very good” category. These findings demonstrate that the integration of Zep Quiz into IPAS instruction effectively enhances students’ critical thinking skills by fostering interactive, engaging, and motivating learning experiences that encourage active participation and deeper cognitive processing.